Acute effects of static stretching of hamstring on performance and anterior cruciate ligament injury risk during stop-jump and cutting tasks in female athletes - Ruan, M.; Zhang, Q.; Wu, X. (The Journal of Strength and Conditioning Research, 2017)
There is limited research investigating antagonist stretch. The purpose of this study was to evaluate the influence of static stretching of hamstrings (SSH) on performance and anterior cruciate ligament (ACL) injury risk during stop-jump and 180° cutting tasks. Twelve female college athletes (age 20.8 ± 0.7 years; height 1.61 ± 0.05 m; mass 54.25 ± 4.22 kg) participated in this study. Subjects performed stop-jump and 180° cutting tasks under 2 conditions: after warm-up with 4 × 30 seconds SSH or after warm-up without SSH. Three-dimensional kinematic and kinetic data as well as electromyography of biceps femoris, rectus femoris, vastus medialis, and gastrocnemius medialis were collected during testing. Static stretching of hamstrings significantly enhanced jump height by 5.1% (p = 0.009) but did not change the takeoff speed of cutting. No significant changes in peak knee adduction moment or peak anterior tibia shear force were observed with SSH regardless of the task. The peak lateral tibia shear force during cutting was significantly (p = 0.036) reduced with SSH. The co-contraction of hamstring and quadriceps during the preactivation (stop-jump: p = 0.04; cutting: p = 0.05) and downward phases (stop-jump: p = 0.04; cutting: p = 0.05) was significantly reduced after SSH regardless of the task. The results suggest that SSH enhanced the performance of stop-jump because of decreased co-contraction of hamstring and quadriceps but did not change the performance of cutting. In addition, SSH did not increase ACL injury risk during stop-jump and cutting tasks and even reduced medial-lateral knee loading during cutting.